2019
DOI: 10.1073/pnas.1814597116
|View full text |Cite
|
Sign up to set email alerts
|

Bipotent stem cells support the cyclical regeneration of endometrial epithelium of the murine uterus

Abstract: The endometrial epithelium of the uterus regenerates periodically. The cellular source of newly regenerated endometrial epithelia during a mouse estrous cycle or a human menstrual cycle is presently unknown. Here, I have used single-cell lineage tracing in the whole mouse uterus to demonstrate that epithelial stem cells exist in the mouse uterus. These uterine epithelial stem cells provide a resident cellular supply that fuels endometrial epithelial regeneration. They are able to survive cyclical uterine tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 40 publications
10
62
0
Order By: Relevance
“…Group 2 was characterized by preferential expression of Ltf and Foxa2 . Based on glandular-specific expression of FOXA2 ( Jin, 2019 ; Fig. 1 D), this group was annotated as the glandular epithelium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Group 2 was characterized by preferential expression of Ltf and Foxa2 . Based on glandular-specific expression of FOXA2 ( Jin, 2019 ; Fig. 1 D), this group was annotated as the glandular epithelium.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, two studies based on cell lineage tracing with tamoxifen-controlled Cre expression have been published ( Jin, 2019 ; Syed et al, 2020 ). The first study used limited labeling and mathematical analysis in Krt19-Cre/ERT2 and FoxA2-Cre/ERT2 mice crossed with reporter mice ( Jin, 2019 ) and concluded that the stem cell population resides in the intersection zone between luminal and glandular epithelium. By contrast, the second study reported that Axin2 + glandular cells can act as drivers of epithelial homeostasis and regeneration ( Syed et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the physiological and pathological changes in the endometrium during remodeling are well characterized, the cellular mechanisms that drive the programmed events of the endometrial tissue remodeling are still not completely understood. Recent studies provide evidence for endometrial stem cell (ESC) populations that contribute to endometrial regeneration and repair [14,15]. However, these studies have either used rodent models that does not experience menstrual shedding or artificial mouse models with administration and withdrawal of exogenous progesterone rather than the naturally menstruating women with declining hormone levels caused by the demise of corpus luteum.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have suggested location of stem cells in either the glandular (Kaitu'u-Lino et al, 2010) or luminal (Chan and Gargett, 2006;Huang et al, 2012;Jin, 2019) compartments of the mouse endometrial epithelium. In humans, such cells are commonly thought to be located in the basalis segment of the endometrial glands (Nguyen et al, 2012;Patterson et al, 2013;Valentijn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%